Criminal Liability for the Perpetrator of Fraud with the Modus of Lending Motorized Vehicles - Agustina, Enjelia Putri; Fadhilah, Nisa (West Science Law and Human Rights, 2025)
Fraud in the form of borrowing motor vehicles under false pretenses is a type of crime that exploits trust in social relationships and is often overlooked in legal discussions. This study aims to analyze the application of Article 378 of the Indonesian Criminal Code and judicial considerations in determining criminal liability in fraud cases using the case study of Decision Number 102/Pid.B/2024/PN Kotabumi. The research employs a normative juridical method using literature and document analysis to examine the legal framework and factual evidence. Findings indicate that the elements of fraud, both objective and subjective, were fulfilled convincingly. The court imposed a 2-year and 6-month prison sentence, considering both juridical and non-juridical aspects. This study highlights the importance of distinguishing fraud from civil disputes in cases involving personal relationships and emphasizes the necessity for consistent law enforcement to ensure justice and legal certainty.